Enriched Environment Contributes to the Recovery from Neurotoxin-Induced Parkinson’s Disease Pathology - Daphne Alcalá-Zúniga; Erika Espinoza-Torres; Ranjit Kumar Das; Magaly Vargas; Oscar Maldonado; Omar Benavides; Arvind Manojkumar; Roberto de la Garza; Natalia Davila; Isaac Perez; Alejandro Hernandez Martinez; Deepa Roy; et al. (Molecular Neurobiology, 2024)
Parkinson’s disease (PD) is a neurological disorder that affects dopaminergic neurons. The lack of understanding of the underlying molecular mechanisms of PD pathology makes treating it a challenge. Several pieces of evidence support the protective role of enriched environment (EE) and exercise on dopaminergic neurons. The specific aspect(s) of neuroprotection after exposure to EE have not been identified. Therefore, we have investigated the protective role of EE on dopamine dysregulation and subsequent downregulation of DJ1 protein using in vitro and in vivo models of PD. Our study for the first time demonstrated that DJ1 expression has a direct correlation with dopamine downregulation in PD models and exposure to EE has a significant impact on improving the behavioral changes in PD mice. This research provides evidence that exercise in EE has a positive effect on PD without interfering with the current line of therapy.